The potential role of sciatic nerve stiffness in the limitation of maximal ankle range of motion - Andrade, Ricardo J. (Sci Rep, 2018)
It is a long held belief that maximal joint range of motion (ROM) is restricted by muscle tension. However, it exists indirect evidence suggesting that this assumption may not hold true for some joint configurations where non-muscular structures, such as the peripheral nerves, are stretched. Direct evidences are lacking. This study aimed to determine whether a static stretching aiming to load the sciatic nerve without stretch within plantar flexors is effective to: (i) alter nerve stiffness; and (ii) increase the ankle’s maximal ROM. Passive maximal ankle ROM in dorsiflexion was assessed with the hip flexed at 90° (HIP-flexed) or neutral (HIP-neutral, 0°). Sciatic nerve stiffness was estimated using shear wave elastography. Sciatic nerve stretching induced both a 13.3 ± 7.9% (P < 0.001) decrease in the nerve stiffness and a 6.4 ± 2.6° increase in the maximal dorsiflexion ROM assessed in HIP-flexed. In addition, the decrease in sciatic nerve stiffness was significantly correlated with the change in maximal ROM in dorsiflexion (r = −0.571, P = 0.026). These effects occurred in the absence of any change in gastrocnemius medialis and biceps femoris stiffness, and ankle passive torque. These results demonstrate that maximal dorsiflexion ROM can be acutely increased by stretching the sciatic nerve, without altering the muscle stiffness.